Studi Kasus: Minimnya Pembelajaran Berbasis Eksperimen pada Mata Pelajaran Biologi di SMA Nahdlatul Ulama Padangsidimpuan - Adinda Fadillah; Venna Marshaulina Sihombing; Syakilah K. Fahmi Panggabean; Widya Arwita; Aswarina Nasution (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
This study aims to examine the problem of the lack of implementation of experiment-based learning in Biology subjects at SMA Nahdlatul Ulama Padangsidimpuan. The method used is descriptive qualitative with a case study approach, with data collection through interviews with Biology teachers and literature studies. The results showed that limited laboratory facilities, lack of practicum tools and materials, and limited learning time allocation were the main obstacles in the implementation of practicum. Although teachers realize the importance of experimental activities in improving students' understanding and science process skills, structural support from schools is still very limited. In response to these obstacles, several alternatives such as the utilization of virtual laboratories, the use of experimental videos, and simple experiments based on local resources have been attempted. This research recommends strengthening educational policies that support practicum-based learning through the provision of adequate infrastructure, continuous training for teachers, and development of alternative learning media. Thus, Biology learning can be more effective in fostering students' scientific skills and critical thinking according to the demands of the 21st century.